Preparation and Microwave Absorbing Properties of an Electroless Ni-Co Coating on Multiwall Carbon Nanotubes Using [Ag(NH3)2]+ as Activator. (1st October 2015) - Li, Qiao-ling; He, Xiao-yong; Zhang, Yue-qing; Yang, Xiao-feng
Abstract : Ni-Co-coated carbon nanotubes (CNTs) composites with different molar ratios of Ni/Co were synthesized using [Ag(NH3 )2 ] + as activator andH 2 P O 2 - as reductant, thereby replacing the conventional noble metal Pd salt activator and Sn 2+ reductant. Scanning electron microscopy, X-ray diffraction, and X-ray energy dispersive spectrometry analyses demonstrated that the CNTs were deposited with a dense, uniform Ni-Co coating. The possible mechanism of the electroless method was studied, which indicates that pure Ag 0 acted as a nucleation site for subsequent Ni-Co-P deposition. Network vector analyzer measurements indicated that the composite with only Ni coated had an absorbing value of −12.6 dB and the composite with a Ni/Co ratio of four had the maximum wave absorption (−15.6 dB) and the widest absorption bandwidth (800 MHz, RL < −10 dB), while the saturation magnetization (Ms) was 4.28 emu· g −1 and the coercive force (Hc) was 31.33 Oe.